ECSIT is essential for RANKL-induced stimulation of mitochondria in osteoclasts and a target for the anti-osteoclastogenic effects of estrogens - Marques-Carvalho, Adriana; Sardão, Vilma A.; Kim, Ha-Neui; Almeida, Maria (Frontiers in Endocrinology, 2023)
Estrogens inhibit bone resorption and preserve bone mass, at least in part, via direct effects on osteoclasts. The binding of RANKL, the critical cytokine for osteoclast differentiation, to its receptor in osteoclast precursor cells of the monocyte lineage recruits the adaptor protein TRAF6 and activates multiple signaling pathways. Early effects of RANKL include stimulation of mitochondrial complex I activity, oxidative phosphorylation, and production of ATP. 17β-estradiol (E2) prevents these early effects of RANKL on mitochondria and promotes mitochondria mediated apoptotic cell death. However, the molecular mechanisms responsible for the actions of RANKL and estrogens on mitochondria remain unknown. Evolutionarily Conserved Signaling Intermediate in Toll Pathway (ECSIT) is a complex I-associated protein that regulates immune responses in macrophages following the engagement of Toll-like receptors, which also recruit TRAF6. Here, we examined whether ECSIT could be implicated in the rapid effects of RANKL and E2 on osteoclast progenitors. We cultured bone marrow-derived macrophages from C57BL/6 mice with RANKL with or without E2. Using mitochondria-enriched fractions, co-immunoprecipitation assays, and western blotting, we found that RANKL promoted ECSIT-TRAF6 interaction and increased the levels of ECSIT in mitochondria. E2 abrogated these effects of RANKL. Silencing of ECSIT using shRNA decreased osteoclast differentiation and abrogated the inhibitory effects of E2 on osteoclastogenesis. Loss of ECSIT decreased complex I activity, oxygen consumption, NAD+/NADH redox ratio, and ATP production. Loss of ECSIT also decreased mitochondrial ROS and mitochondria membrane potential. In the absence of ECSIT, the stimulatory actions of RANKL on complex I activity and all other markers of oxidative phosphorylation, as well as their inhibition by E2, were prevented. Instead, RANKL stimulated apoptosis of osteoclast progenitors, suggesting that dysregulated mitochondria cause a switch in RANKL signaling from pro-survival to pro-apoptotic. Overall, our results indicate that ECSIT represents a central node for the early effects of RANKL on mitochondria and that inhibition of ECSIT-mediated mitochondria stimulation might contribute to the bone protective actions of estrogens.